The Renaissance of KRAS Targeting in Advanced Non-Small-Cell Lung Cancer: New Opportunities Following Old Failures - Ferrara, Miriam Grazia; Stefani, Alessio; Pilotto, Sara; Carbone, Carmine; Vita, Emanuele; Di Salvatore, Mariantonietta; D’Argento, Ettore; Sparagna, Ileana; Monaca, Federico; Valente, Giustina; Vitale, Antonio; Piro, Geny; et al. (Frontiers in Oncology, 2021)
Non-small cell lung cancer (NSCLC) represents the perfect paradigm of ‘precision medicine’ due to its complex intratumoral heterogeneity. It is truly characterized by a range of molecular alterations that can deeply influence the natural history of this disease. Several molecular alterations have been found over time, paving the road to biomarker-driven therapy and radically changing the prognosis of ‘oncogene addicted’ NSCLC patients. Kirsten rat sarcoma (KRAS) mutations are present in up to 30% of NSCLC (especially in adenocarcinoma histotype) and have been identified decades ago. It works as oncogene and it is involved in the intricate multistep cancer development, affecting tumor pathogenesis and histology. Since its discovery, its molecular characteristics and its marked affinity to a specific substrate have led to define KRAS as an undruggable alteration. Despite that, many attempts have been made to develop drugs capable of targeting KRAS signaling but, until a few years ago, these efforts have been unsuccessful. Comprehensive genomic profiling and wide-spectrum analysis of genetic alterations have only recently allowed to identify different types of KRAS mutations. In particular, it has been demonstrated that the most common KRAS mutation, the G12C variant, can be targeted with allele-specific covalent inhibitors and switched in the inactive state. This tricky step has finally opened new frontiers in the treatment approach of KRAS-mutant patients and might hopefully increase their prognosis and quality of life. In addition to the exciting advent of direct target agents, the most attractive challenge in KRAS signaling inhibition concerns many preclinical and clinical efforts to indirectly interfere with KRAS activity, by targeting guanine nucleotide exchange factors (GEFs), by inhibiting the active KRAS state (GTP-bond) and by altering the epigenetic proteins involved in KRAS activation. Moreover, the few available evidence demonstrate that epigenetic impact may differ among specific NSCLC histologies and molecular backgrounds, deserving a deeper knowledge of these mechanisms. In this review, we aim to highlight the most interesting aspects of (epi)genetic KRAS features, hoping to light the way to the state of art of targeting KRAS in NSCLC.